a Review of Antecedents of Job Embeddedness Among Nurses in Privat Sector Hospital - Bratajaya, Ika Mardiyah; Wijaya, Dodi; Ardiana, Anisa (Universitas Malahayati, 2024)
ABSTRACT High nurse turnover can lead to a shortage of experienced staff, increase the workload for those remaining, and potentially lead to dissatisfaction and negatively impact patient safety and hospital performance. One of the most important factors predicting the decision to change jobs among nurses is the level of job embeddedness. Knowing the antecedent factors of job embeddedness in nurses in the private hospital sector. This research uses the literature study method, using 3 databases by entering keywords that are adjusted to the standard Boolean Operators keywords. This study consisted of 10 articles from various countries. Several antecedent factors of job embeddedness were found in this study, especially in private hospitals. Of the 9 antecedent factors found in this literature review, researchers grouped them into 2 (two) major groups, including individual factors and organizational factors. Individual factors consist of self-efficacy, professional self-concept, work craft, and perceived well-being. Meanwhile, environmental factors consist of leadership, breach of contract, work environment, quality of relationship between leaders and team members (LMX), and work life (values, fairness, community, and control). These findings underscore the importance of developing organizational strategies that support nurses' individual development, create a positive work environment, and consider values, fairness, community, and control in an effort to strengthen nurses' work attachment and maintain their retention in the long term. Keywords: Nurses, Work Engagement, Health Care, Private Sector ABSTRAK Turnover perawat yang tinggi dapat menyebabkan kekurangan staf yang berpengalaman, meningkatkan beban kerja bagi yang tersisa, dan berpotensi menyebabkan ketidakpuasan serta berdampak negatif pada keselamatan pasien dan kinerja rumah sakit. Salah satu faktor terpenting yang memprediksi keputusan untuk berpindah secara sukarela pada kalangan perawat adalah tingkat job embeddedness. Mengetahui faktor antesenden job embeddedness pada perawat di sector rumah sakit swasta. This study uses the literature review method, using 3 databases by entering keywords adjusted to the standard Boolean Operators keyword. Penelitian ini terdiri dari 10 artikel dari berbagai negara. Beberapa factor anteseden job embeddedness ditemukan dalam penelitian ini, khususnya di rumah sakit swasta. Dari 9 faktor anteseden yang ditemukan dalam tinjauan pustaka ini, peneliti mengelompokkannya menjadi 2 (dua) kelompok besar, antara lain faktor individu dan faktor organisasi. Faktor individu terdiri dari efikasi diri, konsep diri profesional, kerajinan kerja, dan perceived well-being. Sementara itu, faktor lingkungan terdiri dari kepemimpinan, pelanggaran kontrak, lingkungan kerja, kualitas hubungan antara pemimpin dan anggota tim (LMX), serta kehidupan kerja (nilai, keadilan, komunitas, dan kontrol). Temuan ini menggarisbawahi pentingnya pengembangan strategi organisasi yang mendukung perkembangan individu perawat, menciptakan lingkungan kerja yang positif, serta mempertimbangkan nilai-nilai, keadilan, komunitas, dan kontrol dalam upaya memperkuat keterikatan kerja perawat dan menjaga retensi mereka dalam jangka panjang. Kata Kunci: Perawat, Keterikatan Kerja, Pelayanan Kesehatan, Sektor Swasta